Punishment, political economy and crisis: Disciplining labour through state-corporate surveillance in the ‘neoliberal heartlands’ - Xenakis, Sappho (European journal of criminology, 2022)
The aim of this article is to advance the politico-economic analysis of punishment in contexts of crisis. To this end, the article examines punitive state interventions in the ‘neoliberal heartlands’ of the UK and the US, as set against a backdrop of multidimensional crises that have reconfigured political landscapes, the relationship between labour and capital, and the mode and scope of state punishment. Through a focus on the treatment of socio-economically embedded undocumented migrants, the article highlights the increasingly diffuse punitive repercussions stemming from the growing multi-sectoral, corporate-facilitated surveillance of the labour force.